STRENGTHENING PANCASILA CORE VALUES IN ANTICIPATING RADICALISM IN THE GLOBAL ERA FOR THE YOUTH GENERATION IN JAMBI PROVINCE: Indonesia - Alif Aditya Candra; M. Lukman Hakim; Sundari Utami; Tanty Riyani (ESTUNGKARA, 2022)
Radicalism is an understanding that can disrupt the integrity of the nation. Based on data from the Badan Nasional Penanggulangan Terorisme (BNPT), the Indonesia radicalism potential index in 2021 is 12.2%, which is dominated by the youth generation. Various efforts need to be made to minimize the development of radicalism among the youth generation, one of the efforts that can be applied is by strengthening Pancasila core values ​​for the youth generation. This public devotion activity is carried out in the form of seminars in the Rectorate Hall of the University of Jambi and online via zoom and youtube with as many as 400 participants from the youth generation in Jambi province aged 17-23 years. The method of implementing the activities is divided into three, starting from the planning stage, the implementation stage, and the evaluation stage. The seminar was held in three sessions, the first session is an opening session on the challenges of radicalism in the global era for the younger generation, the second session is a deepening session on strengthening Pancasila values ​​to face the real challenges of radicalism for the younger generation, and the third session is an interactive dialogue between participants and presenter. The seminar activities succeeded in providing understanding to participants and inspiring participants to apply Pancasila core values ​​in anticipating radicalism in their daily lives.